Zirconium-based materials for fluoride removal from aqueous environments: A literature review and scientometric analysis - Savari, Arezo; Hamidi, Ali; Farjadfard, Sima; Omidvar, Mohsen; Ramavandi, Bahman (Colloid and interface science communications, 2023)
The unique characteristics of zirconium have made it susceptible to use in the pollutants purification. Although various zirconium-adsorbents have been used to remove fluoride, but no review article examines their perspective of the practical application. This article reviewed defluoridation papers using Zr-adsorbents. The modification of adsorbents with zirconium was found a useful technique to increase the fluoride adsorption capacity. Researchers have modified many materials like activated carbon, zeolite, and activated alumina by zirconium for efficient fluoride removal and among them Zr-doped polypyrrole/Zr iodate composite (183.5 mg/g) and CeO2-ZrO2 nanocages (175 mg/g) have a great capacity. Zirconium improves the chemistry and morphology of materials for fluoride adsorption. The Zr-materials were reusable and their mechanisms in fluoride removal were mostly electrostatic and ion exchange. Due to the excellent feature of zirconium, explorations can be continued to provide adsorbents with a higher ability to eliminate fluoride or similar pollutants. [Display omitted] •Research on fluoride removal using Zr-materials was visualized using CiteSpace.•Research interest on Zr-based materials as adsorbents is dramatically increasing.•Fluoride adsorption capacity of 4–183 mg/g has been reported for Zr-materials.•Adsorption of fluoride using Zr-materials mostly obey pseudo-second order model.•Activated carbon, zeolite, and activated alumina was mostly modified by Zr.